Demographic, behavioural and physician‐related determinants of early melanoma detection in a low‐incidence population. (14th September 2014) - Talaganis, J.A.; Biello, K.; Plaka, M.; Polydorou, D.; Papadopoulos, O.; Trakatelli, M.; Sotiriadis, D.; Tsoutsos, D.; Kechagias, G.; Gogas, H.; Antoniou, C.; Swetter, S.M.; et al.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Few studies have addressed the impact of various clinical, demographic and behavioural parameters in the detection of early vs. late or thin vs. thick melanomas. What does this study add? Our study was conducted in a population with high case fatality and provides stronger evidence on behavioural factors associated with melanoma thickness that can now be translated to public health initiatives. Skin self‐examination was significantly associated with the detection of early melanoma.